Surgical Strategies for Epilepsy in Developing Countries: Experience with SEEG in Temporal Lobe Epilepsy - Oddo, Silvia Andrea (2021)
Introduction: In this work we present the evidence that in a developing country, it is possible toperform surgical treatment for drug resistant temporal lobe epilepsy patients, including those casesthat require SEEG, with a similar outcome than in developed countries.Methods: We selected 19 consecutive drug resistant temporal lobe epilepsy patients, whounderwent SEEG evaluation at El Cruce Hospital from 2014 to 2019. SEEG is performed due tofailure to localize the Epileptogenic Zone (EZ) with non-invasive methods, when the hypothesis ofEZ are suspected to involve extra temporal areas, negative MRI, suspected bilateral onset, bilateralhippocampal lesion, or with discrepancies between MRI findings and scalp Video-EEG monitoring.The implantation scheme was planned based on the EZ hypothesis, based on scalp Video-EEG,especially ictal clinical semiology, neuroimaging data and neuropsychological results. Between 6and 12 multilead electrodes per patient were implanted, in temporal and extra temporal areas.Results: Thirteen patients (68.4%) with unilateral EZ were found eligible for surgery after SEEG.Seven patients underwent a mesial temporal region resection (left N=3, right n=4). One patientunderwent a frontotemporal corticectomy, one patient an insulectomy. Because of the pandemicsituation, four patients are on a list for surgery. Six patients were formally excluded from surgerybecause of the bilateral (seizures originating independently or concomitantly in both temporallobes) or multifocal origin of their seizures.Conclusion: According to the results obtained in this case analysis, we consider SEEG to be anappropriate method to define EZ in patients with drug-resistant temporal epilepsy and thesubsequent indication for surgery. We hope to encourage the multiplication of epilepsy surgerycenters in the region that have specialist staff and financial resources. Despite the high costs, it isachievable development with the same quality as that carried out in developed countries.